SMS notification service for book due / Diana Natasha Md. Yusof - Md. Yusof, Diana Natasha (Faculty of Computer and Mathematical Sciences, 2006)
Short Message Service (SMS) is a huge popular communication technology for mobile phones, as many user sending billions of text messages to each other every years. According to the statistics from Malaysian Communication and Multimedia Commission, 4.5 billion SMS message has been sent by Malaysians. The aim of the project was to send the SMS notification service for the book overdue. The project was built using a SMS delivery mechanism for the library to notify of book dues that was similar to the existing email notification of book dues, the SMS system was ensure notification reaches to user immediately without requiring user to have internet access. Using existing mobile technology, the library could improve their services by being able to reach out to user anytime and anywhere.